Pengaruh Pelayanan Pemeriksaan Keamanan di Passengers Security Check Point (PSCP) Terhadap Kepuasan Penumpang di Unit Aviation Securityc (AVSEC) Bandar Udara Internasional Supadio Pontianak - Febriyanti Salsa Billa; Aditya Dewantari (CV. Aksara Global Akademia, 2023)
One aspect that supports and optimizes the security and safety of passengers is Aviation Security (AVSEC) flight security personnel. The purpose of this study was to find out whether there was an influence of Aviation Security (AVSEC) inspection services at Passengers Security Check Point (PSCP) Supadio Pontianak International Airport on passenger satisfaction and to find out how much influence there was between Aviation Security (AVSEC) security check services at Passengers Security Check Point (PSCP) Supadio Pontianak International Airport for passenger satisfaction. The method used in this study is a quantitative method using data analysis techniques, namely instrument testing, hypothesis testing, simple linear regression testing, and coefficient of determination testing. The sampling technique used is non-probability sampling with a sample of 100 respondents who are users of air transport services at Supadio Pontianak International Airport and who have passed inspection at the Passengers Security Check Point (PSCP). The research results concluded that; first Ha was accepted because there was an influence between the performance of Aviation Security (AVSEC) officers on passenger satisfaction at Supadio Pontianak International Airport as evidenced by the T count 15,445 > T table 1.948 and the sig value 0.00 <0.05. Second, it is known that the R square is 0.709, which means that the effect of the independent variable (AVSEC Officer Service) on the dependent variable (Passenger Satisfaction) is 70.9%.